Platelet-rich plasma (PRP) in osteoarthritis (OA) knee: Correct dose critical for long term clinical efficacy - Bansal, Himanshu; Leon, Jerry; Pont, Jeremy L.; Wilson, David A.; Bansal, Anupama; Agarwal, Diwaker; Preoteasa, Iustin (Scientific reports, 2021)
Despite encouraging results reported with regards to Platelet-rich plasma (PRP) application in osteoarthritis (OA) knee, still critical issues like conclusive structural evidence of its efficacy, standard dose and good manual method of preparation to obtain high yield remains unanswered. Present study is an attempt to optimise the dose and concentration of therapeutic PRP and its correlation with structural, physiologic efficacy with a new manual method of PRP preparation. A total of one hundred and fifty patients were randomized to receive either PRP (10 billion platelets) or hyaluronic acid (HA; 4 ml; 75 patients in each group) and followed up till 1 year. An addition of filtration step with 1 µm filter in manual PRP processing improved platelet recovery upto 90%. Significant improvements in WOMAC (51.94 ± 7.35 vs. 57.33 ± 8.92; P < 0.001), IKDC scores (62.8 ± 6.24 vs 52.7 ± 6.39; P < 0.001), 6-min pain free walking distance (+ 120 vs. + 4; P < 0.001) persisted in PRP compared to HA group at 1 year. Significant decline IL-6 and TNF-α levels observed in PRP group ( P < 0.05) compared to HA at 1 month. Study demonstrated that an absolute count of 10 billion platelets is crucial in a PRP formulation to have long sustained chondroprotective effect upto one year in moderate knee OA.